The Effect of Family Visit Management on Anxiety Levels Among Patients in the Intensive Care Unit: A Scoping Review - Ajeng Andini Sutisnu; Firman Sugiharto; Henny Yulianita; Theresia Eriyani (Universitas Muhammadiyah Surakarta, 2023)
Several studies identified the effect of family visits on reducing patient and family anxiety levels. However, until now there has been no review that synthesizes the results of these studies on this population. This review aimed to identify the effect of family visit management on the anxiety level of patients and families in the ICU. This Study used a scoping review method using CINAHL, PubMed, Science Direct and search engines Google Scholar. The keywords used in English were